Simulation of the cutting action of a single PDC cutter using DEM - Joodi, B.; Sarmadivaleh, Mohammad; Rasouli, V.; Nabipour, A. (2012)
Optimization of costly drilling operations is essential to reduce the overall costs of oil and gas extraction. Simulation of these operations can yield a better selection of parameters for maximum drilling efficiency. One of the most cost efficient methods to do so is by computer modeling. Because of the complex nature of the cutting process, no analytical methods can be used for its modeling and the numerical methods are the only option. FEM and Discrete Element Method (DEM) are the most commonly used numerical methods for this purpose. One of the best features of the DEM is that it is very suitable for discontinuous environment and no special treatment or process is required in tracking the produced cracks and fragmentation. Also depending on the depth of cut, it can both simulate ductile or brittle failures. In current study, a 2D computer model was developed using the particle flow code (PFC2D) to simulate the cutting action of a single cutter. PFC uses the DEM to model a rock sample by fine cylinders or disks. The properties of the Berea sandstone were considered in our modeling. A good match of mechanical properties was obtained for the rock model by adjusting micro parameters of the contacts between the constituting balls and the results of the simulation are compared to laboratory data. © 2012 WIT Press.